Sleep deprivation, pain and prematurity: a review study - Kelly Cristina Santos de Carvalho Bonan; João da Costa Pimentel Filho; Rosana Maria Tristão; José Alfredo Lacerda de Jesus; Dioclécio Campos Junior (Arquivos de Neuro-Psiquiatria)
The aim was to describe current reports in the scientific literature on sleep in the intensive care environment and sleep deprivation associated with painful experiences in premature infant. A systematic search was conducted for studies on sleep, pain, premature birth and care of the newborn. Web of Knowledge, MEDLINE, LILACS, Cochrane Library, PubMed, EMBASE, Scopus, VHL and SciELO databases were consulted. The association between sleep deprivation and pain generates effects that are observed in the brain and the behavioral and physiological activity of preterm infants. Polysomnography in intensive care units and pain management in neonates allow comparison with the first year of life and term infants. We have found few references and evidence that neonatal care programs can influence sleep development and reduce the negative impact of the environment. This evidence is discussed from the perspective of how hospital intervention can improve the development of premature infants.